A method for removing chromium nitride coating on the surface of glass forming mold and treating waste liquid
By removing the chromium nitride coating removal method, nitride in the prior art was solved by using an oxidant preoxidation and a removal solution composed of ammonia triacetic acid complexing agent and hydrogen peroxide, and combined with the hydrothermal reaction to treat the waste liquid, nitriding in the prior art was solved The chromium coating removal process is complex and environmental pollution problems, achieving rapid and environmentally friendly removal effects and non-toxic treatment of waste liquids.
Patent Information
- Application Number
- CN202211421360.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-15
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-11-15
AI Technical Summary
The existing chromium nitride coating removal methods have problems such as complex process, long deplating time, easy corrosion of the substrate, and environmental pollution. In particular, the removal effect of chromium nitride coating is poor, and chromium-containing ion waste is ignored. liquid treatment.
After pre-oxidation treatment with an oxidant, the glass molding mold is placed in a removal liquid composed of ammonia triacetic acid complexing agent and hydrogen peroxide for insulation reaction to achieve the removal of the chromium nitride coating. At the same time, a chromium manganese-aminotriacetic acid coordination polymer was prepared by hydrothermal reaction and a hydrothermal reaction to treat the waste liquid to achieve non-toxic treatment of the waste liquid.
The rapid and thorough removal of chromium nitride coating is achieved, the matrix corrosion is avoided, and environmental pollution is solved through non-toxic treatment, reducing the production cost of glass products.
Smart Images

Figure CN116103662B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of stripping chromium nitride hard coating on the surface of a mould, and in particular relates to a method for stripping chromium nitride coating on the surface of a glass forming mould and treating waste liquid. Background Art
[0002] Plating chromium nitride (CrN) hard coating on the surface of stainless steel glass forming molds can effectively improve the surface mechanical properties, anti-friction and anti-oxidation capabilities of the molds, thereby meeting the needs of glass product molding. However, with the long-term use of the mold, the surface coating often becomes damaged and aged, affecting the glass molding effect. In order to reuse the mold, the surface damaged coating needs to be completely removed and then re-plated. At present, the chromium nitride hard coating is mainly removed by electrolytic stripping, that is, the mold, inert electrode and reference electrode are placed in the electrolyte using the principle of the electrolytic cell to construct a two-electrode or three-electrode reaction system, and the hard coating is removed by electrochemical oxidation-reduction (patent: CN101565850A). This electrochemical stripping technology has the advantages of rapid reaction and thorough stripping. However, the construction of the electrolytic cell will undoubtedly increase the production cost, and the voltage range and current density must be strictly controlled during the reaction process, otherwise the substrate will also be corroded, which makes the stripping process more complicated.
[0003] The chemical stripping method with stripping liquid as the core has the advantages of simple process, no requirements on mold shape, and low cost. For example, alkaline stripping liquid (sodium hydroxide-hydrogen peroxide-based stripping liquid) or acidic stripping liquid (nitric acid-hydrofluoric acid-based stripping liquid) are widely used for the stripping of nitride hard coatings such as titanium nitride, titanium aluminum nitride, and titanium zirconium nitride. Compared with titanium-based nitride, chromium nitride is superior in structural stability, corrosion resistance, and bonding strength with the substrate. Although it is beneficial to the protection of the mold, it leads to poor stripping effect of commonly used acidic or alkaline stripping liquids on chromium nitride coatings. Patent CN101457365A mentions a method of removing chromium nitride from the surface of the substrate by mixing alkaline and acidic stripping solutions, that is, first immersing the sample coated with chromium nitride in an alkaline solution composed of potassium permanganate and hydroxide (sodium hydroxide or / and potassium hydroxide), taking out the sample after 10-30 minutes, washing the substrate with water and drying it; then immersing the sample in an acidic solution (one or more of sulfuric acid, nitric acid, and hydrochloric acid) for 10-60 seconds, then washing the substrate with water and drying it, and repeating the above experimental steps until the film layer is completely removed. This method is complex in process, and the alternating and repeated use of acid-base stripping solutions places high demands on the acid and alkali resistance of the substrate, and is not suitable for steel mold substrates. In addition, both the electrolytic method and the stripping solution method only focus on the stripping effect of the chromium nitride coating, ignoring the chromium ion (Cr 3+ Cr 6+ )Treatment of wastewater. Chromium ions, especially Cr 6+It is listed in the first batch of toxic and hazardous water pollutants due to its high toxicity and difficulty in degradation. Therefore, it is imperative to treat the chromium-containing waste liquid generated during the removal process in a non-toxic and harmless manner. Summary of the invention
[0004] In view of the problems existing in the conventional method of stripping chromium nitride coating, such as complex process, long stripping time, easy corrosion of substrate, environmental pollution, etc., the present invention provides a method for stripping chromium nitride coating on the surface of glass forming mold and treating waste liquid, constructing a stripping method with rapid stripping, no damage to substrate, simple components and low cost, so as to solve the problem of difficult stripping of chromium nitride coating.
[0005] The present invention is achieved through the following technical solutions:
[0006] A method for removing chromium nitride coating on the surface of a glass forming mold, characterized in that the glass forming mold coated with the chromium nitride coating is pre-oxidized using an oxidant, and then the mold after the pre-oxidation treatment is placed in a stripping liquid for a certain period of time to achieve the removal of the chromium nitride coating on the mold surface;
[0007] The stripping solution is composed of a nitrilotriacetic acid complexing agent and hydrogen peroxide, and the mass ratio of the nitrilotriacetic acid complexing agent to the hydrogen peroxide is 1:100 to 20:100;
[0008] The oxidant is one or more of potassium permanganate solution, potassium ferrate solution and potassium dichromate solution.
[0009] Preferably, the mass concentration of the potassium permanganate solution is 1-10%, the mass concentration of the potassium ferrate solution is 1-30%, and the mass concentration of the potassium dichromate solution is 1-20%.
[0010] Preferably, the nitrilotriacetic acid complexing agent is one or more of nitrilotriacetic acid monosodium salt, nitrilotriacetic acid disodium salt, nitrilotriacetic acid trisodium salt, nitrilotriacetic acid monopotassium salt, nitrilotriacetic acid dipotassium salt, nitrilotriacetic acid tripotassium salt, nitrilotriacetic acid sodium potassium salt and hydrates thereof; and the mass fraction of hydrogen peroxide is 1-45%.
[0011] Preferably, the nitrilotriacetic acid complexing agent is trisodium nitrilotriacetate; and the mass fraction of the hydrogen peroxide is 10%.
[0012] Preferably, the pre-oxidation temperature is 5-95° C., and the pre-oxidation time is 0.1-48 h; the insulation reaction temperature is 0-80° C., and the reaction time is 1-720 min.
[0013] Preferably, the glass forming mold is a stainless steel mold, the thickness of the chromium nitride coating is 0.1-100 μm, and the stainless steel component is one of 14Cr17Ni2, 06Cr19Ni10, and 1Cr18Ni9.
[0014] In the present invention, the method for treating the waste liquid generated by the stripping method comprises adding nitrilotriacetic acid to the waste liquid, performing a hydrothermal reaction, filtering, washing and drying to obtain a chromium-nitrilotriacetic acid coordination polymer; the waste liquid is the stripping liquid that can no longer effectively strip the chromium nitride on the surface of the glass forming mold after repeated use, and the solution components include hydrogen peroxide, nitrilotriacetic acid-chromium ion complex, sodium ion or potassium ion; in addition, according to different types of pre-oxidants, it also includes one or two of nitrilotriacetic acid-manganese ion complex and nitrilotriacetic acid-iron ion complex.
[0015] Preferably, the mass ratio of the nitrilotriacetic acid waste liquid is 0.1:100-10:100; the hydrothermal reaction temperature is 120-200° C., and the reaction time is 0.5-48 h.
[0016] Preferably, the mass ratio of nitrilotriacetic acid to waste liquid is 1:100; the hydrothermal reaction temperature is 180° C., and the reaction time is 6 hours.
[0017] Preferably, the washing is rinsing with deionized water; and the drying is drying at 25-120° C. for 1-48 hours.
[0018] The present invention starts from the physical and chemical properties of the chromium nitride hard film and the glass forming mold substrate and combines the research on the stripping mechanism to construct a stripping liquid and a corresponding stripping process with rapid stripping, no damage to the substrate, simple components and low cost, in order to solve the problem of difficult stripping of chromium nitride coating. At the same time, in combination with the national environmental protection requirements and the composition characteristics of the chromium-containing stripping waste liquid, it is treated to be non-toxic and the metal elements are recycled to establish a green production process template.
[0019] The present invention can achieve the destruction of the chemical stability of the chromium nitride coating through a simple pre-oxidation treatment, so that it can be removed by a stripping liquid, and the stripping liquid is composed of hydrogen peroxide and nitrilotriacetic acid complexing agent, which has simple ingredients, low cost, and both components are non-toxic, easy to degrade, and environmentally friendly; during the reaction process, there is no need to add strong alkali (sodium hydroxide, potassium hydroxide) and strong acid (nitric acid, hydrofluoric acid), the chromium nitride coating on the mold surface is quickly stripped, and the weakly alkaline stripping liquid is non-corrosive to the surface of the stainless steel mold. The further waste liquid disposal process exerts the reduction and coordination effects of nitrilotriacetic acid in the hydrothermal process to achieve the reduction of the chromium ion valence and the preparation of chromium-nitrilotriacetic acid coordination polymer crystals. This material has potential application value in the fields of adsorption, catalysis, energy storage, etc.
[0020] Therefore, compared with the traditional process, the process of removing the chromium nitride coating on the surface of the glass forming mold and treating the chromium-containing waste liquid of the present invention is more concise, efficient, green and environmentally friendly. Moreover, the surface of the stainless steel mold after stripping is smooth and corrosion-free, and can be recycled after repeated coating, which greatly reduces the production cost of glass products.
[0021] Beneficial Effects
[0022] The process for removing the chromium nitride coating on the surface of the glass forming mold and treating the chromium-containing waste liquid of the present invention is more concise, efficient, green and environmentally friendly. The surface of the stainless steel mold after the chromium nitride coating is removed is smooth and corrosion-free, and can be recycled after repeated coating, which greatly reduces the production cost of glass products. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 These are digital photos of the chromium nitride coating on the surface of the glass forming mold in Example 1 before and after pre-oxidation and removal;
[0024] Figure 2 The surface scanning electron microscope image and element spectrum analysis of the chromium nitride coating on the surface of the glass forming mold in Example 1 after pre-oxidation;
[0025] Figure 3 The surface scanning electron microscope images and element composition comparison of the chromium nitride coating on the surface of the glass forming mold in Example 1 before and after removal;
[0026] Figure 4 The X-ray diffraction pattern of chromium manganese-nitrilotriacetic acid crystals after the waste liquid treatment in Example 1;
[0027] Figure 5 This is a scanning electron microscope image of chromium manganese-nitrilotriacetic acid crystals after the waste liquid treatment in Example 1. Specific implementation methods
[0028] The present invention is further described below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to illustrate the implementation method of the present invention, and are not used to limit the operation and operating scope of the present invention, and the changes derived therefrom are still within the protection scope of the claims of the present invention.
[0029] Unless otherwise defined, all professional and scientific terms used in the present invention have the same meanings as those understood by technicians in the technical field of the present invention. Unless otherwise specified, the drugs or reagents used in the present invention are used in accordance with the product instructions or the conventional methods of use in the field. The process of the present invention is further described based on the drawings and specific embodiments of the specification.
[0030] The glass forming mold described in the following embodiments is a stainless steel mold; the thickness of the chromium nitride coating is 3 μm, and the stainless steel component is 14Cr17Ni2.
[0031] Example 1
[0032] (1) The glass forming mold coated with chromium nitride coating was immersed in a 5% potassium permanganate solution and pre-oxidized at 60°C for 4 hours;
[0033] (2) Immerse the pre-oxidized glass forming mold in a stripping solution (1.5 kg of trisodium nitrilotriacetate dissolved in 10 L of 10% hydrogen peroxide to prepare a stripping solution) and react at 25°C for 60 minutes to achieve complete stripping of the film layer. The stripping solution can be used repeatedly until the chromium nitride coating can no longer be stripped, and the waste liquid is collected;
[0034] (3) placing the waste liquid in a hydrothermal reactor, adding nitrilotriacetic acid, with the mass ratio of nitrilotriacetic acid to waste liquid being 1:100, and conducting a hydrothermal reaction at 180°C for 6 hours;
[0035] (4) The reactants of the hydrothermal reaction are filtered, washed with deionized water, and dried at 60°C for 12 h to obtain a solid powder, which is the corresponding coordination polymer.
[0036] The effect of removing the chromium nitride coating on the surface of the glass forming mold in this embodiment was observed, and it was found that the color of the mold surface changed from grayish white to grayish black (after pre-oxidation treatment) to silvery white (such as Figure 1 As shown); the microscopic morphology was analyzed and it was found that after pre-oxidation treatment, the stable chromium nitride coating would be oxidized by the oxidant to form a flaky structure containing manganese / chromium oxide components (such as Figure 2 As shown); after further stripping liquid treatment, scanning electron microscopy observation and elemental analysis results showed that the chromium nitride component on the surface of the stainless steel mold had disappeared and the mold surface remained flat without corrosion (as shown Figure 3 shown);
[0037] The solid powder obtained in the process of removing the waste liquid in the embodiment is subjected to X-ray diffraction pattern analysis to determine that the obtained solid powder is a chromium manganese-nitrilotriacetic acid coordination polymer crystal (such as Figure 4 Further scanning electron microscopy images confirmed that the coordination polymer crystal microstructure is a nanowire morphology ( Figure 5 as shown).
[0038] Example 2
[0039] (1) A glass forming mold coated with a chromium nitride coating was immersed in a 10% by mass potassium ferrate solution and pre-oxidized at 50°C for 6 hours;
[0040] (2) Immerse the pre-oxidized glass forming mold in a stripping solution (0.5 kg of trisodium nitrilotriacetate dissolved in 10 L of 20% by mass hydrogen peroxide to prepare a stripping solution) and react at 40°C for 30 minutes to achieve complete stripping of the film layer. The stripping solution can be used repeatedly until the chromium nitride coating can no longer be stripped, and collect the waste liquid;
[0041] (3) placing the waste liquid in a hydrothermal reactor, adding nitrilotriacetic acid, with the mass ratio of nitrilotriacetic acid to waste liquid being 5:100, and conducting a hydrothermal reaction at 160°C for 12 hours;
[0042] (4) The reactants of the hydrothermal reaction are filtered, washed with deionized water, and dried at 40°C for 24 hours to obtain a solid powder, which is the corresponding coordination polymer.
[0043] Example 3
[0044] (1) The glass forming mold coated with chromium nitride coating was immersed in a 10% by mass potassium permanganate solution and pre-oxidized at 80°C for 2 h;
[0045] (2) Immerse the pre-oxidized glass forming mold in a stripping solution (1.5 kg of trisodium nitrilotriacetate dissolved in 10 L of 30% by mass hydrogen peroxide to prepare a stripping solution) and react at 5°C for 120 minutes to achieve complete stripping of the film layer. The stripping solution can be used repeatedly until the chromium nitride coating can no longer be stripped, and collect the waste liquid;
[0046] (3) placing the waste liquid in a hydrothermal reactor, adding nitrilotriacetic acid, with the mass ratio of nitrilotriacetic acid to waste liquid being 10:100, and subjecting the reaction to hydrothermal reaction at 180°C for 12 hours;
[0047] (4) The reactants of the hydrothermal reaction are filtered, washed with deionized water, and dried at 60°C for 10 h to obtain a solid powder, which is the corresponding coordination polymer.
[0048] Example 4
[0049] (1) The glass forming mold coated with chromium nitride coating was immersed in a 15% by mass potassium dichromate solution and pre-oxidized at 50°C for 4 hours;
[0050] (2) Immerse the pre-oxidized glass forming mold in a stripping solution (2 kg of trisodium nitrilotriacetate dissolved in 15 L of 30% by mass hydrogen peroxide to prepare a stripping solution) and react at 50 ° C for 10 minutes to achieve complete stripping of the film layer. The stripping solution can be used repeatedly until the chromium nitride coating can no longer be stripped, and the waste liquid is collected;
[0051] (3) placing the waste liquid in a hydrothermal reactor, adding nitrilotriacetic acid, with the mass ratio of nitrilotriacetic acid to waste liquid being 1:100, and conducting a hydrothermal reaction at 150°C for 16 hours;
[0052] (4) The reactants of the hydrothermal reaction were filtered, washed with deionized water, and dried at 70°C for 16 h to obtain a solid powder, which is the corresponding coordination polymer.
[0053] Example 5
[0054] (1) The glass forming mold coated with chromium nitride coating was immersed in a mixed solution of 5% potassium permanganate solution and 10% potassium ferrate solution at 25°C for pre-oxidation for 12 hours;
[0055] (2) Immerse the pre-oxidized glass forming mold in a stripping solution (0.6 kg of trisodium nitrilotriacetate dissolved in 10 L of 15% by mass hydrogen peroxide to prepare a stripping solution) and react at 25°C for 60 minutes to achieve complete stripping of the film layer. The stripping solution can be used repeatedly until the chromium nitride coating can no longer be stripped, and the waste liquid is collected;
[0056] (3) placing the waste liquid in a hydrothermal reactor, adding nitrilotriacetic acid, with the mass ratio of nitrilotriacetic acid to waste liquid being 20:100, and conducting a hydrothermal reaction at 180°C for 12 hours;
[0057] (4) The reactants of the hydrothermal reaction are filtered, washed with deionized water, and dried at 50°C for 12 h to obtain a solid powder, which is the corresponding coordination polymer.
[0058] Example 6
[0059] (1) Immerse the glass forming mold coated with chromium nitride coating in a mixed solution of 5% potassium permanganate solution and 5% potassium dichromate solution at 5°C for pre-oxidation for 24 hours;
[0060] (2) Immerse the pre-oxidized glass forming mold in a stripping solution (0.8 kg of trisodium nitrilotriacetate dissolved in 10 L of 15% hydrogen peroxide to prepare a stripping solution) and react at 15°C for 120 minutes to achieve complete stripping of the film layer. The stripping solution can be used repeatedly until the chromium nitride coating can no longer be stripped, and the waste liquid is collected;
[0061] (3) placing the waste liquid in a hydrothermal reactor, adding nitrilotriacetic acid, with the mass ratio of nitrilotriacetic acid to waste liquid being 15:100, and conducting a hydrothermal reaction at 180°C for 8 hours;
[0062] (4) The reactants of the hydrothermal reaction are filtered, washed with deionized water, and dried at 50°C for 12 h to obtain a solid powder, which is the corresponding coordination polymer.
[0063] Example 7
[0064] (1) The glass forming mold coated with chromium nitride coating was immersed in a potassium permanganate solution with a mass fraction of 8% and pre-oxidized at 25°C for 24 hours;
[0065] (2) Immerse the pre-oxidized glass forming mold in a stripping solution (1 kg of tripotassium nitrilotriacetate dissolved in 10 L of 25% by mass hydrogen peroxide to prepare a stripping solution) and react at 45°C for 40 minutes to achieve complete stripping of the film layer. The stripping solution can be used repeatedly until the chromium nitride coating can no longer be stripped, and collect the waste liquid;
[0066] (3) placing the waste liquid in a hydrothermal reactor, adding nitrilotriacetic acid, with the mass ratio of nitrilotriacetic acid to waste liquid being 10:100, and subjecting the reaction to hydrothermal reaction at 180°C for 10 hours;
[0067] (4) The reactants of the hydrothermal reaction are filtered, washed with deionized water, and dried at 50°C for 12 h to obtain a solid powder, which is the corresponding coordination polymer.
[0068] Example 8
[0069] (1) The glass forming mold coated with chromium nitride coating was immersed in a mixed solution of 10% by mass potassium permanganate solution and 5% by mass potassium dichromate solution, and pre-oxidized at 60°C for 6 hours;
[0070] (2) Immerse the pre-oxidized glass forming mold in a stripping solution (1 kg of disodium nitrilotriacetate dissolved in 15 L of 15% hydrogen peroxide to prepare a stripping solution) and react at 65°C for 5 minutes to achieve complete stripping of the film layer. The stripping solution can be used repeatedly until the chromium nitride coating can no longer be stripped, and collect the waste liquid;
[0071] (3) placing the waste liquid in a hydrothermal reactor, adding nitrilotriacetic acid, with the mass ratio of nitrilotriacetic acid to waste liquid being 30:100, and conducting a hydrothermal reaction at 160°C for 10 hours;
[0072] (4) The reactants of the hydrothermal reaction are filtered, washed with deionized water, and dried at 80°C for 12 h to obtain a solid powder, which is the corresponding coordination polymer.
Claims
1. A method for removing chromium nitride coating on the surface of a glass forming mold, characterized in that: The glass forming mold coated with chromium nitride coating is pre-oxidized by using an oxidant, and then the mold after pre-oxidation is placed in a stripping liquid for a certain period of time to achieve the stripping of the chromium nitride coating on the mold surface; The stripping liquid is composed of a nitrilotriacetic acid complexing agent and hydrogen peroxide, and the mass ratio of the nitrilotriacetic acid complexing agent to the hydrogen peroxide is 1:100 to 20:100; the nitrilotriacetic acid complexing agent is one or more of nitrilotriacetic acid monosodium salt, nitrilotriacetic acid disodium salt, nitrilotriacetic acid trisodium salt, nitrilotriacetic acid monopotassium salt, nitrilotriacetic acid dipotassium salt, nitrilotriacetic acid tripotassium salt, nitrilotriacetic acid sodium potassium salt and hydrates thereof; The oxidant is one or more of potassium permanganate solution, potassium ferrate solution and potassium dichromate solution.
2. The method for removing chromium nitride coating on the surface of a glass forming mold according to claim 1, characterized in that: The mass concentration of the potassium permanganate solution is 1-10%, the mass concentration of the potassium ferrate solution is 1-30%, and the mass concentration of the potassium dichromate solution is 1-20%.
3. The method for removing chromium nitride coating on the surface of a glass forming mold according to claim 1, characterized in that: The mass fraction of the hydrogen peroxide is 1-45%.
4. The method for removing chromium nitride coating on the surface of a glass forming mold according to claim 3, characterized in that: The mass fraction of the hydrogen peroxide is 10%.
5. The method for removing chromium nitride coating on the surface of a glass forming mold according to claim 1, characterized in that: The nitrilotriacetic acid complexing agent is nitrilotriacetic acid trisodium salt.
6. The method for removing chromium nitride coating on the surface of a glass forming mold according to claim 1, characterized in that: The pre-oxidation temperature is 5-95°C, and the pre-oxidation time is 0.1-48h; the insulation reaction temperature is 0-80°C, and the reaction time is 1-720min.
7. The method for removing chromium nitride coating on the surface of a glass forming mold according to claim 1, characterized in that: The glass forming mold is a stainless steel mold, the thickness of the chromium nitride coating is 0.1-100 μm, and the stainless steel component is 14Cr 17 Ni2, 06Cr 19 Ni 10 1Cr 18 One of Ni9.
Citation Information
Patent Citations
Removing liquid of chromium nitride film layer and removing method of film layer
CN101565850A
Method for removing chromium nitride film on base material surface
CN101457365A
Aqueous solution and method for the formation of a passivation layer
CN103492612A